Metabolic and bioenergetic drivers of neurodegenerative disease : neurodegenerative disease research and commonalities with metabolic diseases - Soderbom, Grazyna; Esterline, Russell; Oscarsson, Jan; Mattson, Mark Paul (International review of neurobiology, 2020)
"Metabolic Drivers and Bioenergetic Components of Neurodegenerative Disease summarizes recent developments in intervention trials in neurodegenerative diseases, particularly Alzheimer's and Parkinson's, as well as increasing evidence for the overlap between drivers of metabolic and neurodegenerative disease that impact mitochondrial function and bioenergetics, and subsequently cellular function and pathophysiology. Topics covered include Brain Glucose and Ketone Utilization in Brain Ageing and Neurodegenerative Diseases; the Mitochondrial Hypothesis: Dysfunction, Bioenergetic Defects, and the Metabolic Link to Alzheimer's Disease; the Metabolic Impact on Neuroinflammation and Microglial Modulation in Neurodegenerative Diseases, the Impact of Circadian and Diurnal Rhythms on Cellular Metabolic Function and Neurodegenerative Diseases, and much more."--Publisher's web page, viewed July 30, 2020